2005
DOI: 10.1556/abiol.56.2005.1-2.10
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of paraquat toxicity in maize leaves by benzyladenine

Abstract: The protective effect of a cytokinin benzyladenine (BA), against toxicity of paraquat (PQ), a widely used herbicide and a well-known oxidative stress inducer, was investigated in the leaves of maize. Maize leaves have been pretreated with BA at concentrations of 1, 10 and 100 microM and afterwards treated with PQ. At all concentrations tested, BA retarded PQ-induced decreases in chlorophyll, carotenoid and ascorbic acid contents. Pretreatment with 10 and 100 microM of BA significantly increased superoxide dism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…This suggested that the reduced production of H 2 O 2 in the presence of BA supplementation might be the result of increased peroxidase activity more than catalase. Such a protective effect of BA against oxidative stress has been reported previously and explained as BA affecting the activity of POX (Durmuş and Kadioğlu 2005). The presence of AgNPs in the seed culture medium at a low concentration (1 mg L −1 ) improved the impact of BA on the activities of microshoot antioxidant enzymes, but higher doses of AgNPs (2.5 and 5 mg L −1 ) considerably reduced POX activity in propagated shoots.…”
Section: Resultssupporting
confidence: 72%
“…This suggested that the reduced production of H 2 O 2 in the presence of BA supplementation might be the result of increased peroxidase activity more than catalase. Such a protective effect of BA against oxidative stress has been reported previously and explained as BA affecting the activity of POX (Durmuş and Kadioğlu 2005). The presence of AgNPs in the seed culture medium at a low concentration (1 mg L −1 ) improved the impact of BA on the activities of microshoot antioxidant enzymes, but higher doses of AgNPs (2.5 and 5 mg L −1 ) considerably reduced POX activity in propagated shoots.…”
Section: Resultssupporting
confidence: 72%
“…in the present study, sod activity significantly increased in the leaves treated with diuron for, respectively, 48 and 72 h. similarly, increases in sod activity have been observed in response to treatment with herbicides paraquat, diquat, diuron, atrazine and prometryne [17,18,24,33]. In the present study, the effects of polyamines on sod activity were different according to the polyamine tested and time after diuron treatment.…”
Section: Discussionsupporting
confidence: 76%
“…The activity of peroxidases was enhanced in tobacco transformed by the ipt gene (Schnablová et al. , 2006), and an enhancement of peroxidase activity after the exogenous application of benzyladenine to maize leaves has also been described (Durmus and Kadioglu, 2005). The results described in this paper, together with previously published data, indicate that enhanced cytokinin content in plant tissues raises the levels of peroxidases and laccases, the synthesis of electron acceptor precursor and the level of cytokinin dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%